Financial leverage and value creation by textile manufacturing SMEs in the city of Bogotá - Ducón Salas, Julio Cesar (2023)
Given that the initial purpose of any company is to grow and last, external financing is considered, by definition, as a means to achieve short and long-term objectives. However, the input of these resources is often used to cover deficit situations, which does not always improve their results or lead to the objectives that have been established. In this sense, the article presents an analysis of the financial leverage of five textile manufacturing companies and their relationship with a group of risk indicators. Furthermore, this relationship was characterized by a group of financial and operational drivers. Said analysis was carried out with a quantitative approach based on the financial statements of these companies, which were the raw material to prepare the aforementioned study. The research process concluded that leverage, contrary to what was expected in the selected sample, was more related to negative results than to capital growth, an aspect that is corroborated with the characterization by means of financial and operational inductors.